Mobilizing Domestic Funds for the HIV/AIDS Response in Nigeria: Estimating the Potential Contribution of the National Health Insurance Scheme. (1st April 2023) - Oladele, Tolulope T.; Olakunde, Babayemi O.; Mao, Wenhui; Oladele, Edward Adekola; Ogundipe, Alex; Yamey, Gavin; Ogbuoji, Osondu
Abstract : Background: Amid the dwindling donor support for HIV in Nigeria, there is an urgent need for additional domestic HIV funding. This study estimates the required financial resources for people living with HIV (PLHIV) and the potential magnitude of domestic resources for HIV through the National Health Insurance Scheme (NHIS) and by prioritizing HIV within the health budget. Methods: We estimated the resource needs for providing antiretroviral therapy (ART) to adults, children, and pregnant women living with HIV under 3 scenarios: current coverage rates, coverage rates based on historical trends, and a rapid scale-up situation. We conducted a fiscal space analysis to estimate the potential contribution from macroeconomic growth, the NHIS, and prioritizing HIV within the health budget from 2020 to 2025. Results: At current coverage rates, the annual treatment costs for adults would range between US$ 505 million in 2020 to US$ 655 million in 2025; for children, it ranges from US$ 33.5 million in 2020 to US$ 32 million in 2025. The annual costs of providing PMTCT at current coverage rates range from US$ 65 million in 2020 to US$ 72 million in 2025. An additional US$ 319 million could potentially be generated between 2020 and 2025 through the NHIS for HIV. Prioritizing HIV within the health budget can generate an additional US$ 686 million. Conclusion: Substantial domestic funds can be mobilized by these means to sustain the HIV response. However, because this additional funding may not be sufficient to cover all PLHIV, a phased approach, initially prioritizing certain populations such as children or pregnant women, is recommended.